The Effect of Education and Training and Work Environment on Teacher’s Performance - Agustini, Evasari; Ahmad, Syarwani; Eddy, Syaiful (Journal of Social Work and Science Education, 2023)
The purpose of this study is to examine and assess the effect of education and training and work environment on teacher’s performance. This study uses quantitative research methods and the research design is in the form of an influence study, to determine the effect between the independent variables and the dependent variable. The findings demonstrated that there is a significant effect of the education and training and work environment partially and simultaneously on the performance of State Junior High School teachers in Pemulutan District. The novelty of this article, where the school will have good teacher’s performance, all stakeholders should create good work environment and give chance for teachers’ education and training.